Exploring the general practitioners’ perception of the inter-professional care of rheumatoid arthritis patients (GEPRA—II): a qualitative interview study - Anne-Laure Yailian; Audrey Janoly-Dumenil; Emmanuelle Vignot; Aurélie Fontana; Charline Estublier; Cyrille Confavreux; Roland Chapurlat; Claude Dussart; Humbert de Freminville (BMC Primary Care)
Abstract Background A lack of medication adherence among patients with rheumatoid arthritis (RA) has been reported. Inter-professional collaborations seem essential for an optimal therapeutic management of patients. The aim of this study was to analyse the barriers and facilitators of general practitioners (GPs) for the implementation of collaborative support programmes in RA. Methods A qualitative semi-structured study using face-to-face or telephone interviews was conducted. Eligible participants included French GPs referring patients with RA. Interviews were audio-recorded and then transcribed. Data were analysed using Braun and Clarke’s thematic analysis framework with Nvivo®12 software. Results Nineteen GPs were interviewed between August 2019 and February 2020. Five themes were identified in the care of their patients with RA. GPs reported being mainly involved in diagnosis and orientation, and frequently asked for pain management and explanation/reformulation of previously given information. They perceived their patients to be adherent to their treatments, although they frequently identified reasons for non-adherence. Regarding their perception of the community-hospital relationship, they sometimes considered it insufficient and expected more immediate interactions. Additionally, most interviewed GPs had no expectation regarding increased collaborations with community pharmacists (CPs) and several GPs were motivated to be more involved in a patient support programme. However, barriers were identified: lack of time and training, and insufficient payment. Conclusions The implementation of a collaborative patient support programme in RA should be developed taking into account the barriers and facilitators identified by GPs who appeared to be aware of the causes of potential non-adherence, and were particularly interested in receiving more information about the therapeutic monitoring of patients by hospital professionals.